Development of Digital Teaching Materials Based on Differentiated Learning Assisted by Artificial Intelligence to Improve Students’ Historical Literacy - Umamah, Nurul; Zulfikar, Fachri; Hilmiah, Anis Syatul; Hartono, Fernanda Prasky; Shodiq, Pasang Budy All (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop of digital teaching materials based on differentiated learning assisted by artificial intelligence to improve students’ historical literacy. This research was conducted as research and development by following the ASSURE research and development procedure. The research subjects were high school students in Banyuwangi city, and the research instruments used questionnaires, interviews and observations, and the data analysis. techniques used quantitative and qualitative data analysis techniques. The research results revealed that (1) the majority of students expressed interest in using digital teaching materials, (2) Students hoped that teaching materials in the form of electronic books could facilitate the learning process from anywhere. (3) Although students have known various histories and cultures in Banyuwangi, only a few know the historical background of a culture in Banyuwangi, and (4) Digital history teaching material products based on differentiation with the help of artificial intelligence products about the history of the Gandrung dance are suitable for use in the learning process in the classroom. The results of this research and development show a 2-tailed significance value for the experimental class of 0.000. Therefore, it can be concluded that the experimental class has a 2-tailed significance value <0.05, which means H0 is rejected. This proves that the Gandrung dance history teaching material has a positive influence on improving historical literacy.